A structural investigation of the short stories of Katherine Mansfield with special reference to the idea of the true and false self - Geldenhuys, M F (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1974)
A survey of the available literature on Katherine Mansfield has shown that, in the five decades which have elapsed since the author's death, critical interest has gradually, but significantly, altered its direction. Despite the workmanlike assessments of such critics as David Daiches in Britain and Andre Maurois in France, and the recognition of her mastery of the short story form by such fellow practitioners of the art as H.E. Bates and Elizabeth Bowen, the mainstream of criticism tended, in the first decades after the author's death, to centre less upon the characteristics of the work itself than upon a cult- like fascination, initiated, perhaps, by the perceptive but over-interested pen of Middleton Murry. Only more recently has this tendency been superseded by a more rigorous scrutiny of the stories themselves; thus the excellence of the author 's technique has now become a major concern. Recent recognition has been accorded, too, to the fact that the stories were in the vanguard of their time with regard to the choice of, as well as the treatment of, theme. Intro. p. 1-2.
Keywords: Mansfield, Katherine, 1888-1923 -- Criticism and interpretation; Short stories; Self in literatur